Analisis Hubungan Citra Merk dan Kualitas Produk Terhadap Kepuasan Konsumen Pengguna Kendaraan Listrik di Indonesia - Wafi, Raihan Fadhlil; Maulana, Noveri (Research Center and Case Clearing House (RC-CCH) - Sekolah Tinggi Manajemen PPM, 2024)
This study aims to analyze the influence of brand image and product quality on customer satisfaction in the electric vehicle industry in Indonesia. A strong brand image and high-quality products are critical factors for electric vehicle manufacturers to build consumer trust and increase sales. In the context of the growth of electric vehicles as an environmentally friendly alternative, this research is grounded in the concepts of customer satisfaction, brand image, and product quality. The study employs a quantitative approach, utilizing a survey involving 154 respondents who are users of two- and four-wheeled electric vehicles. The collected data were analyzed using multiple linear regression to examine the partial and simultaneous effects of the two independent variables on the dependent variable. The results show that brand image and product quality have a significant positive influence, both partially and simultaneously, on customer satisfaction. These findings contribute theoretically to the marketing literature by reinforcing the role of brand image and product quality in enhancing customer satisfaction. Furthermore, the results can be useful for the electric vehicle industry in Indonesia in efforts to improve customer satisfaction through the optimization of brand image and the quality of products offered.